Neferine suppresses osteoclast differentiation through suppressing NF‐κB signal pathway but not MAPKs and promote osteogenesis. Issue 12 (24th May 2019) - Chen, Shenao; Chu, Bingxiang; Chen, Yao; Cheng, Xun; Guo, Di; Chen, Lihua; Wang, Jiacheng; Li, Zhiyan; Hong, Zhenghua; Hong, Dun
Abstract: Osteoporosis is an ageing disease characterized by elevated osteoclastic bone resorption resulting in bone loss, decrease bone strength, and elevated incidence of fractures. Neferine, a natural compound isolated from the traditional Chinese medicine Nelumbo nucifera (Lotus), has been reported exhibit anti‐inflammatory, antioxidant, and anticancer properties. However, its effect on bone remains to be determined. Here we showed that Neferine inhibits RANKL‐induced osteoclast formation in a dose‐ and time‐dependent manner. Furthermore, Neferine also demonstrated antiresorptive properties by effectively ameliorating the bone resorptive activity of mature osteoclasts. Mechanistically, Neferine suppressed RANKL‐induced activation of NF‐κB signaling pathway. This in turn hindered the induction and activation of NFATc1 resulting in downregulation of osteoclast marker genes closely related to differentiation, fusion as well as bone resorption. Interestingly, we found Neferine enhanced the differentiation and bone mineralization activity of MC3T3‐E1 preosteoblast cells. Finally, mice treated with Neferine was protected against ovariectomy (OVX)‐induced bone loss. The Neferine treatment improved bone volume following ovariectomy and also exhibited less TRAP‐positive osteoclasts on bone surface. Collectively our data provide promising evidence that Neferine could be a potential therapeutic application for against osteolytic bone conditions such as osteoporosis. Abstract : Our article first described the role of Neferine in osteoblast differentiation and osteoclast differentiation. Our experiment confirmed for the first time that Neferine has antiosteoporosis in animals.